Pelatihan Pengolahan Limbah Sampah Rumah Tangga Menjadi Eco-Enzim Di Kelurahan Trimurjo - Mariana, Erni; Kinasih, Ayang; Wardany, Kusuma; Rosyidah, Ummi; Qomariyah, Siti (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Garbage is one of the main causes of environmental problems and can damage the balance of the ecosystem. Trimurjo Subdistrict has a lot of organic waste. The objectives of this service are as follows: 1) provide and introduce techniques for converting household organic vegetable waste into eco-enzymes; 2) increase awareness of the importance of converting household waste into economically profitable products. In Trimurjo District, housewives receive direct instructions on how to make eco-enzymes from organic waste. The community, especially housewives, will learn to make eco-enzymes. The brown color and aroma of fermentation will indicate that they are made. After that, the eco-enzyme is processed to produce room fragrance products. The results of this service are: 1). This program has also succeeded in encouraging the community to develop new organic waste processing methods. The results of the response questionnaire that has been explained show that partners are very interested in providing community service. 2). This outreach program succeeded in increasing public awareness about managing organic waste in an environmentally friendly manner.